Contribution of a Cluster Approach to Identify the Profiles of Men Sentenced for Sexual Violence According to Their Risk of Reoffending - Bertsch, Ingrid (Journal of interpersonal violence, 2023)
IntroductionThe aim of this study is to propose a typology of recidivism risk profiles based on the criminogenic needs of a population of men sentenced for sexual violence. Their socio-demographic, criminological, psychological, and psychiatric factors and vulnerabilities are compared. This classification will respond to the need for a better identification of the factors involved in the risk of recidivism of men sentenced for sexual violence, in order to develop more effective management.MethodSeveral psychological and psychiatric scales (personality traits, impulsivity, cognitive distortions, empathy, and psychiatric disorders) were completed by 86 men incarcerated for sexual violence. Their socio-demographic and criminological characteristics were also recorded, and the investigator rated three recidivism scales for all participants. Results: Cluster analysis led to identification of two significantly different needs groups. In contrast to the “Lower needs” profile (n = 54, 64%), the men with a “Higher needs” profile (n = 32, 36%) were significantly younger and less educated had more adult and extra-familial victims, scored higher on Neuroticism and lower on Conscientiousness and Empathy, and presented with more past and current psychiatric disorders.DiscussionThe overall findings of this study are consistent with the literature on the characteristics of men sentenced for sexual violence with high needs. The assessment and management of men who have committed sexual violence must consider: criminogenic factors, which should be prioritized; past or present psychiatric disorders, which may act as acute risk factors; and non-criminogenic needs, which should not be prioritized, but which may (when linked to criminogenic needs) impact the effectiveness of management.